2005
DOI: 10.1016/j.ejcts.2005.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation according to the open lung concept attenuates pulmonary inflammatory response in cardiac surgery☆

Abstract: OLC ventilation leads to an attenuated inflammatory response, presumably by reducing additional lung injury after cardiac surgery. Studies on cytokines after cardiac surgery should take these findings into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
2
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 27 publications
2
62
2
6
Order By: Relevance
“…However, when PEEP was continually adjusted to maintain full endexpiratory alveolar recruitment, less activation of these early inflammatory signalling cascades was found. Similar findings were recently reported in humans [44][45][46][47].…”
Section: Biotraumasupporting
confidence: 92%
“…However, when PEEP was continually adjusted to maintain full endexpiratory alveolar recruitment, less activation of these early inflammatory signalling cascades was found. Similar findings were recently reported in humans [44][45][46][47].…”
Section: Biotraumasupporting
confidence: 92%
“…These patient groups were appropriate models of short-term ventilation in patients who, although without preexisting lung injury, are at risk of ALI. The results of these studies have been mixed, with some investigators showing increases in serum and bronchoalveolar lavage markers of injury 10,[13][14][15][16]19 whereas others have not. 11,12,17,18 There have been remarkably few trials examining clinical outcomes associated with low tidal volume ventilation strategies in otherwise healthy populations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, despite biologic plausibility and considerable retrospective data to support limiting tidal volume in all ventilated patients, equipoise remains regarding optimal tidal volume in non-ALI patients. Although various groups of surgical patients, but especially cardiac surgical patients, have been observed, [8][9][10][11][12][13][14][15][16][17][18][19][20] these investigations have focused primarily on surrogate outcomes measures, leaving a lack of clarity regarding optimal perioperative ventilator strategy.…”
mentioning
confidence: 99%
“…Wrigge et al 20 also found decreased TNF-a levels in the bronchoalveolar lavage samples of their coronary artery bypass graft (CABG) patients. Reis Miranda et al 21 found that the levels of pro-inflammatory cytokine levels decreased more rapidly in patients who were ventilated with low VT. Zupancich et al 22 also showed a reduced increase in pro-inflammatory cytokine levels (Interleukin-6 and Interleukin-8) after cardiopulmonary bypass, using lung-protective ventilation. Michelet et al 25 showed the same results in oesophagectomy patients.…”
Section: Biochemical Eff Ects Of Lung-protective Ventilationmentioning
confidence: 99%